Rethinking the messianic idea in Judaism - Morgan, Michael L., 1944-; Weitzman, Steven, 1965- (Bloomington, Indiana : Indiana University Press, 2015)
"Over the centuries, the messianic tradition has provided the language through which modern Jewish philosophers, socialists, and Zionists envisioned a utopian future. Michael L. Morgan, Steven Weitzman, and an international group of leading scholars ask new questions and provide new ways of thinking about this enduring Jewish idea. Using the writings of Gershom Scholem, which ranged over the history of messianic belief and its conflicted role in the Jewish imagination, these essays put aside the boundaries that divide history from philosophy and religion to offer new perspectives on the role and relevance of messianism today"--
Introduction / Michael L. Morgan and Steven Weitzman -- Blurred lines and open secrets in early Jewish messianism. Messianism between Judaism and Christianity / Annette Yoshiko Reed -- He that cometh out : on how to disclose a messianic secret / Steven Weitzman -- Between here and eternity in medieval Judaism. Maimonides and the idea of a deflationary messiah / Kenneth Seeskin -- "And the crooked shall be made straight" : twisted messianic visions, and a Maimonidean corrective / Menachem Kellner -- Seeking the symmetry of time : the messianic age in medieval chronology / Elisheva Carlebach -- Messianism and ethics in modern Jewish thought. Messianism and ethics / Matt Goldish -- To infinity and beyond : Cohen and Rosenzweig on comportment toward redemption / Benjamin Pollock -- Levinas and messianism / Michael L. Morgan -- Politics and anti-politics in contemporary Jewish messianism. What Zvi Yehudah Kook wrought : the theopolitical radicalization of religious Zionism / Shai Held -- Messianic religious Zionism and the reintroduction of sacrifice : the case of the Temple Institute / Motti Inbari -- The muted messiah : the aversion to messianic forms of Zionism in modern Orthodox thought / David Shatz -- The divine/human messiah and religious deviance : rethinking Chabad messianism / Shaul Magid -- Messianism between religious and secular imagination. Isadore Isou's Messianism awry / Cosana Eram -- Arthur A. Cohen's messianic fiction / Emily Kopley -- Reading messianically with Gershom Scholem / Martin Kavka.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Messianic era (Judaism); Messianic era (Judaism); RELIGION -- Judaism -- General; RELIGION / Judaism / History; Electronic books